Developing STEM-PjBL worksheet to lift students' critical, creative, and computational thinking skill - Ramadhanti Dwi Indranuddin; Eko Susetyarini; Fuad Jaya Miharja (Universitas Muhammadiyah Malang, 2024)
This research aims to develop STEM-PjBL worksheets on eight-gr ade human excretory system material to lift students' creative, critical, and computational thinking skills. This R&D research uses the Borg & Gall model. The data collection instruments were interview sheets, validation sheets, questionnaire sheets, and also tests (pretest and posttest). The results show that the STEM-PjBL worksheet is feasible and practical as a learning instructional. The data on the effectiveness of learning media obtained an N-gain score of 88.7 (N-gain >70) and is included in the high category, this shows that STEM-PjBL worksheets can improve students' critical thinking skills. The average score for all aspects of the creative thinking assessment was 81% (creative) and the average score for computational thinking skills was 80% (very high). These results show that STEM-PjBL worksheets can improve students' creative, critical, and computational thinking abilities.